Resistance Characteristics of Riparian Plants in South China:A Case Study of Shenzhen River - ZHENG Shaoping; TONG Xiaolei; HU Haonan (Renmin Zhujiang)
The water-blocking characteristics of riparian plants are an important factor affecting the flood discharge capacity of the river.Taking the Shenzhen River as an instance,this paper adopts image analysis remote sensing to analyze the changes in the growth range of riparian plants from 2008 to 2018.Based on the measured flood data and a one-dimensional mathematical model,research combinations of different channel composite roughness are set to quantitatively analyze the influence of the riparian plants on the composite roughness of the river section and then study the degree of influence of riparian plants on flood flow velocity and flood stage.The study shows that from 2008 to 2018,the riparian plants in the middle and lower reaches of the Shenzhen River expanded by nearly 30 m into the river channel.The composite roughness of the river channel increased by about 0.005.In flood conditions of once in 200,100,and 50 years,the water level of the river channel increased by 1.1 m,0.7 m,and 0.5 m,respectively.